PENDEKATAN METODE BERMAIN PERAN UNTUK PENDIDIKAN SEKS ANAK USIA DINI - Alucyana, Alucyana (Generasi Emas, 2018)
Introduce early sex education is very important, so that children are able to fortify itself from sexual crimes. The impact of violence or sexual abuse on early childhood is very influential on their psychological development. Starting from the short-term impact of physical pain, guilt, fear, anxiety, shame, anger, and helplessness. Though the long term is a particular psychological symptom that the victim felt as a trauma that caused the victim to have no trust. Early childhood sex education is an attempt to provide information or knowledge to early childhood about identifying limbs, parts and limb functions, as well as the importance of maintaining limbs, as well as differences in men and women. One of the learning methods used in early childhood is learning while playing. Namely the method of pretend plays or play ostensibly. This game is very effective considering the early age has a vocabulary that is still limited and not able to think abstract to prevent the occurrence of sexual abuse in early childhood.